Vicos Vindiciae. Eine Auseinandersetzung um den Naturrechtsbegriff - Dominik Recknagel (Laboratorio dell'ISPF, 2016)
Vicos Vindiciae. A debate about the legal concept of Nature. After his Principj di una Scienza Nuova, the first draft of his New Science, had received a very limited attention as well as a malevolent and totally misinformed review in the Acta eruditorum, Vico’s response in the Vindiciae was an occasion to express his outrage and to seek vindication for wholly academic and intellectual reasons. So the Vindiciae is a short summary of Vico’s New Science of the common nature of the nations and his new system of natural law. But Vico’s New Science is not a totally new doctrine of natural law. This paper highlights some similarities that can be found between Vico’s principles and those which Christian Thomasius had introduced in his Fundamenta iuris naturae et gentium of 1705.